Intergenerational transmission of left-right ideology: A question of gender and parenting style? - Weiss, Julia (Frontiers in Political Science, 2023)
“Left” and “right” are common concepts when it comes to describing both political attitudes of citizens and politicians or to classifying, for example, parties on the political spectrum. But how do political ideological attitudes emerge? One central factor is political socialization, in which the family is a key socialization agent. However, existing research focuses largely on partisan preferences and how they emerge through family political socialization. Nevertheless, due to multiparty systems, this concept is less suitable in the European context. This paper therefore contributes to filling this research gap by looking at the role of the family as a political socialization agent in the emergence of political ideological attitudes. Hereby the focus is on two key research questions: what difference does the cross-gender transmission of left-right ideology make? How does the parenting style affect intergenerational transmission? These questions are examined using the Cultural Pathways to Economic Self-Sufficiency and Entrepreneurship (CUPESSE) dataset, whose structure allows for several advances on existing studies. First, it contains a high number of cases with more than 4,000 parent-child dyads, which come from a total of 11 European countries and thus allow a view beyond existing single country studies. Furthermore, it contains the classification of the parenting style by the children and thus enables analyses based on the perception of the recipients of the parenting rather than the parent self-assessment. The results of the analysis indicate that existing differences in political ideology between parents and children vary for cross-gender transmission processes. It also shows that the similarity of political ideology between parents and children is influenced by the parenting style, such as whether children experienced warmth from their parents, support in the pursuit of autonomy, or strong controlling behavior.